Pedagogics of Olonkho Spiritual Concept Sphere in Creation of the Culture - Polikarpova, Evdokia Mikhailovna; Nikitina, Nurguyana Gavrilievna (Journal of History Culture and Art Research, 2018)
The article analyzes olonkho as fundamental source of wisdom and the teachings of the ancestors about the sensible life and humanism. In olonkho, we can see portrayals of high moral standards of sensible life, and traditional values, which were skillfully depicted using expressive means and stylistic devices of the Yakut language. Traditional values reflect the imaginative world view, a unique Yakut model of the world and life, which is specifically represented by an entire system of spiritual concepts of a philosophical understanding of the world creation and human life. Many scholars highlight the important role that Platon A. Sleptsov – Oyunsky played in maintaining and popularizing olonkho. In the troublesome years of new political and government relations being established, owing to his efforts and outstanding organizational skills, he collected a valuable scope of olonkho stories from the first-hand source – the olonkho storytellers. Being a repository of philosophical and religious worldviews as well as of pedagogical and educational principles, today, these creative writings are in the center of researchers’ attention. The study of pedagogics and the methods of studying olonkho in schools began in the 1970s. Presently, the search for educators and methodologists in Yakutia is based on the studies of the leading Russian researchers – N.A. Rubakin, M.M. Bakhtin, N.S. Berdyaev, D.S. Likhachov, B.S. Gershunsky, G.D. Gachev, T.D. Polozova, etc. All these scholars regard the perception of language arts as a personal and deep mental process. The following three concept sphere blocks were singled out: 1 – I am a small part of the Universe, 2 – I am a child of nature, 3 – I am an Aiyy person and the creator of life. In this system, the spiritual concept sphere can lead the people step-by-step to learning about the vitally important values and to a deep understanding of their personal “I” and their inner spiritual world. We have proved the didactic necessity to educate students about olonkho in accordance with this concept system.